In Silico Anti-Inflammation Prediction of Glycyrrhiza Extracts Against Covid-19 - Mansoureh Nazari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Due to its anti-inflammation effect, Glycyrrhiza extract is one of the natural extracts that may potentially combat coronavirus disease in 2019 (COVID-19). In the current article, we evaluate in silico (molecular docking) properties of active compounds available in Glycyrrhiza, native to Western Asia, North Africa, and Southern Europe, and compare its anti-inflammation effect with remdesivir as positive compounds based on molecular docking characteristics. The main active compounds were selected based on their significant roles in the pharmacological effects of Glycyrrhiza. The results obtained in this study demonstrated that most of the studied main compounds interacted stronger than selected remdesivir to inhibit the spike protein in COVID-19. The combined scores (binding affinity and drug-likeness properties of the ligand, demonstrated to be the potentially possible COVID-19 inhibitor compared with positive control. The active site analysis of the interactions also showed that Glycyrrhiza extract containing active compounds might have therapeutic effects against COVID-19.